2009
DOI: 10.1111/j.1540-8167.2009.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study to Assess the Efficacy of Rate and Site of Atrial Pacing on Long‐Term Development of Atrial Fibrillation

Abstract: The Septal Pacing for Atrial Fibrillation Suppression Evaluation (SAFE) study is a single-blinded, parallel randomized designed multicenter study in pacemaker indicated patients with paroxysmal atrial fibrillation (AF). The objective is to evaluate whether the site of atrial pacing--conventional right atrial appendage versus low atrial septal--with or without atrial overdrive pacing will influence the development of persistent AF. The study will provide a definitive answer to whether a different atrial pacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…20 The protocol of SAFE has been published previously. 19 Briefly, SAFE was a sin ng g gle-e--bl bl lin in inde de ded, d, d, 2 2x2…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The protocol of SAFE has been published previously. 19 Briefly, SAFE was a sin ng g gle-e--bl bl lin in inde de ded, d, d, 2 2x2…”
Section: Study Protocolmentioning
confidence: 99%
“…It has bee ee en n n pr pr prop op opos os sed ed e t tha ha hat t t re e edu du duct ct ctio i n n n of of of t t tot ot otal al al at at a ri ri r al al al con on ondu du duct ct c io io ion n n ti ime me mes s s a a and nd nd d dis is spe pe pers rs rsio io ion n of atrial randomized controlled trial using clinical AF as the endpoint. The Septal Pacing for AF Suppression Evaluation (SAFE) study 19 was designed to address these uncertainties in pacing strategies for the secondary prevention of progression to persistent AF in patients with SSS. We hypothesized that RA septal pacing with an atrial pacing algorithm to ensure high percentage of atrial pacing can prevent the progression to persistent AF in patients with SSS and paroxysmal AF.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, low atrial septal (LAS) pacing has been recommended instead of RAA pacing to prevent ATA, 16 though this remains to be confirmed by randomized clinical trial. 17 However, because the LAS region is closer to the ventricle than the RAA, it may be associated with a higher likelihood of FFRW oversensing, 16,18 though the prevalence and characteristics of FFRW sensing associated with LAS pacing have not been formally studied.…”
Section: Editorial P 582mentioning
confidence: 99%
“…chest roentgenogram, and (2) a negative P wave in the inferior leads and isoelectric or negative P wave in leads I, V5 and V6 during atrial pacing, on 12-lead ECG (Figures 1B,C). [16][17][18] Statistical Analysis Continuous variables are expressed as means ± standard deviation. Factors influencing the sensing of FFRW were determined using the chi-square test, and between-group comparisons were made by Mann-Whitney's U-test for continuous variables and by Fisher's exact test for dichotomous variables.…”
Section: Implantation Of the Lead In The Lasmentioning
confidence: 99%
“…7-9 Although several small studies have demonstrated the clinical efficacy of this procedure, it has not been proven by a large randomized study. 10 The authors in this issue of the Journal 5 are to be highly recommended for demonstrating the next step in the clinical benefit of this particular method. Figure 1.…”
Section: A Narrower Spacing Of Electrodes and Atrial Septum Pacingmentioning
confidence: 98%